DEVELOPMENT OF INDEPENDENCE IN THE PROCESS OF PROFESSIONAL TRAINING OF THE FUTURE MASTER OF PSYCHOLOGIST UNDER THE CONDITIONS OF SOCIAL CHANGES - Lariontseva, Anna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article analyzed and determined the relevance of the study of the problem of the development of the independence of future masters of psychology in the process of professional training under the conditions of social changes, substantiated the relevance of solving the problem, considered the theoretical issues of the development of the independence of the future master of psychology. The relevance of the study is determined by the deep transformations of the values of being in modern Ukrainian society, connected with the rethinking of human creativity. The realization of this goal in institutions of higher education, in particular in the context of the professional training of future psychologists, is connected with the development and implementation of innovative educational technologies that will be able to activate the development of independence in future specialists. Research methods. To achieve the goal in the work, it is planned to use a set of methods and techniques of scientific knowledge. The results. The importance of the development of independence in the process of professional training of the future Master of Psychology in the conditions of social changes is revealed. Conclusions. Socio-economic transformations that are constantly taking place in society place new demands on the personality of a modern specialist. Modern researchers, such as E. Rapatsevich, L. S. Vygotskyi, V. I. Morosanova and others, almost unanimously note that the increasing pace of development of new technologies, the information "explosion" and the rapid "obsolescence" of information; sharp complication, automation and computerization of production processes; the high probability of occurrence of "non-standard" situations in the industrial and social spheres, put forward new demands on the future masters of psychology